2019
DOI: 10.1182/blood-2019-130113
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Antigen Receptor T Cells Targeting NKG2D-Ligands Show Robust Efficacy Against Acute Myeloid Leukemia and T-Cell Acute Lymphoblastic Leukemia

Abstract: CAR T cell approaches to effectively target AML and T-ALL without off-tumor effects on healthy myeloid or T cell compartments respectively are an unmet medical need. NKG2D-ligands are a promising target given their absence on healthy cells and surface expression in a wide range of malignancies. NKG2D-ligand expression in T-ALL has not previously been interrogated, and reports regarding the prevalence and density of NKG2D-ligand expression in AML vary. A first-in-human clinical trial of CART cells targeting NKG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…HER2 intratumoral heterogeneity, for example, is reported in up to 40% of breast cancers and is a potential mechanism for resistance [ 119 ]. Strategies to overcome intratumoral heterogeneity in solid and hematologic malignancies include using epigenetic modulators to increase surface expression of target antigens [ 120 , 121 , 122 ] and targeting multiple antigens expressed throughout the tumor simultaneously [ 120 , 123 , 124 , 125 ]. Few preclinical studies using these approaches to address tumor heterogeneity in breast cancer models exist, and they will be necessary for the success of these therapies in breast cancer.…”
Section: Identification Of Suitable Tumor Targetsmentioning
confidence: 99%
“…HER2 intratumoral heterogeneity, for example, is reported in up to 40% of breast cancers and is a potential mechanism for resistance [ 119 ]. Strategies to overcome intratumoral heterogeneity in solid and hematologic malignancies include using epigenetic modulators to increase surface expression of target antigens [ 120 , 121 , 122 ] and targeting multiple antigens expressed throughout the tumor simultaneously [ 120 , 123 , 124 , 125 ]. Few preclinical studies using these approaches to address tumor heterogeneity in breast cancer models exist, and they will be necessary for the success of these therapies in breast cancer.…”
Section: Identification Of Suitable Tumor Targetsmentioning
confidence: 99%
“…Targeting FLT3 or CD117 could be an attractive option, again in association with ASCT (Jetani et al 2018;Myburgh et al 2020). Targeting of the Lewis Y antigen and NKG2DL CAR-T cells has also been proposed, but phase 1 trials have shown short response durations, despite reduced toxicity (Ritchie et al 2013;Driouk et al 2019). CAR-T cells targeting CD44v6 mediate potent antitumour effects against AML while sparing normal haematopoietic stem cells (Casucci et al 2013), and a clinical trial is currently ongoing.…”
Section: Single or Dual Antigen Targeting?mentioning
confidence: 99%
“…They found that decitabine exposure upregulates MUC1 on the surface of pancreatic cancer cells, effectively sensitizing tumor cells to in vitro cytolysis by MUC1-specific CAR T cells (Figure 1A). A more recent example for the use of epigenetic agents as sensitizers for CAR T cell therapy is upregulation of ligands of natural killer (NK)G2D by valproic acid, a potent histone deacetylase (HDAC) inhibitor [55]. NKG2D is an activating receptor expressed on the cell surface of NK cells.…”
Section: Pharmaceutical Strategies For Upregulating Car Target Antigens In Cancer Cellsmentioning
confidence: 99%
“…In a first-in-human clinical trial in patients with acute myeloid leukemia (AML), NKG2D ligand-redirected CAR T cells had limited efficacy, which was attributed to insufficient levels of ligand expression on the surface of leukemic blasts of the patients [62]. The same group now found that NKG2D ligand expression on AML blasts can be selectively enhanced by preincubation with valproic acid, resulting in augmented antileukemic activity in functional in vitro assays [55].…”
Section: Pharmaceutical Strategies For Upregulating Car Target Antigens In Cancer Cellsmentioning
confidence: 99%